The genome sequence of the tree of heaven, Ailanthus altissima (Mill.) Swingle, 1916 [version 1; peer review: 2 approved] - Maarten J. M. Christenhusz; Ilia J. Leitch; Rowan J. Schley (Wellcome Open Research, 2023)
We present a genome assembly from an individual Ailanthus altissima (tree of heaven; Streptophyta; Magnoliopsida; Sapindales; Simaroubaceae). The genome sequence is 939 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules. The mitochondrial and plastid genome assemblies are 661.1 kilobases and 161.1 kilobases long, respectively.